(untitled) (Élisée - Revista de Geografía de la Universidad Estatal de Goiás, 2021)
In this text, we will analyze the most used concepts to study the history of Afro-Brazilian religions. First, we will analyze the intellectuals and academics who studied Afro religions throughout the 20th century, using the concept of religious syncretism, showing how these authors used this concept to build an idea of the superiority of some Afro-Brazilian religions in relation to others, based on the idea of “African purity”. We highlight the criticisms and problems generated by the use of this concept and present a conceptual alternative for Afro-Brazilian studies: post-colonial studies and their concept of hybridism. Keywords: Afro-Brazilian religions. Syncretism. Post-colonial studies. Hybridity.